2012
DOI: 10.1111/j.1536-7150.2012.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐Country Analysis of the Risk Factors for Depression at the Micro and Macro Levels

Abstract: Abstract1Past research has provided evidence of the role of some personal characteristics (age, gender, religion) as risk factors for depression. However, few researchers have jointly examined the specific impact of each characteristic and whether country characteristics (economic performance and others environmental factors) change the probability of being depressed. In general, this is due to the use of single‐country databases. The aim of this article is to extend previous findings by employing a much large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Glanz [68] argues that the most often mentioned theoretical model that has not been fully applied in research and practice is the Social Ecological Model; and then suggests that this promising model needs to better articulated, applied and evaluated. Recently, research has shown that SEM is majorly applied in the public and medical health research [42,59,77,78,[87][88][89][90][91][92]. Elder et al [77] observe that SEM is becoming more widely used in health behaviour research.…”
Section: Application Of Social Ecological Model (Sem) In Improving Samentioning
confidence: 99%
“…Glanz [68] argues that the most often mentioned theoretical model that has not been fully applied in research and practice is the Social Ecological Model; and then suggests that this promising model needs to better articulated, applied and evaluated. Recently, research has shown that SEM is majorly applied in the public and medical health research [42,59,77,78,[87][88][89][90][91][92]. Elder et al [77] observe that SEM is becoming more widely used in health behaviour research.…”
Section: Application Of Social Ecological Model (Sem) In Improving Samentioning
confidence: 99%
“…These psychosocial outcomes of inequality may lead to stress-related mental health problems. This view has been supported by empirical evidence among adults such that adults living in unequal countries or regions displayed poor subjective well-being and high rates of mental distress (Burns, Tomita, & Kapadia, 2014;Melgar & Rossi, 2012;Messias, Eaton, & Grooms, 2011;Oishi & Kesebir, 2015;Oishi et al, 2011;Van Deurzen, Van Ingen, & Van Oorschot, 2015).…”
mentioning
confidence: 94%
“…Depression, as proxied in this paper, may not represent the true value of such condition: in fact, a self-reported measure might pick up cultural differences in the description of subjective feelings and may be influenced by time and other factors occurring when the interview was done. However, self-report depression measures are becoming increasingly important (50); then, they can be easily implemented to large samples (51,52).…”
Section: The Statistical Model (Ivp)mentioning
confidence: 99%